Perancangan Interior Restoran Mancanegara di Surabaya - Yonathan, Steven (Intra, 2015)
This interior design of multi-culture restaurant in Surabaya is based on humans main needs, circulation efficiency between the server and the customer, and also the development of restaurateur business in big cities. As the time goes on, interior design at a restaurant has become very important. Therefore, the design in this foreign restaurant is focusing on the function, aesthetics, and also the circulation. This multi-culture restaurant provides three kinds of different menus from three different countries; America, China, and Japan, so people can freely choose their own favorite. The concept applied is also compatible with each of their own culture to make this design more interesting. With so many choice of menus and a comfortable interior for any kind of people, apart from becoming a place to eat and to hang out together, this restaurant can also be used as a business place, such as a meeting place with clients, or to entertain them. The style applied is a modern style with the some variations of colors, shapes, or ornaments that symbolized each of their own countries, so the ambiance in that restaurant will become stronger and less boring.